Intradural Eosinophilic Granuloma Invading Skull: Case Report and Review of the Literature - Mardi, Kavita (Asian J Neurosurg, 2017)
Eosinophilic granuloma is a localized form of Langerhans cell histiocytosis, most commonly involving the skeletal system. Their origin from the dura is rare with only a handful of cases on record. We present one such rare case of an eosinophilic granuloma originating from the dura mater with secondary osseous invasion in an 11-year-old female child who presented with a swelling in the right parietal region. Magnetic resonance imaging demonstrated an enhancing mass with a wide dural attachment with a lytic lesion in the overlying skull. Right parietal extended craniotomy was done with the excision of mass from the dura. Histopathological features of mass were characteristic of eosinophilic granuloma which was confirmed by positive immunohistochemical staining for CD1a.